Examining an In-Home Behavioral Parent Training Protocol Among Parents Who Use Substances Involved Child Welfare: Effectiveness of SafeCare. (November 2022) - Moreland, Angela; Crum, Kathleen; Rostad, Whitney L.; Stefanescu, Andrei; Whitaker, Daniel
Given the detrimental impact of substance use (SU) on both parent and child outcomes including child maltreatment, research and service efforts have focused on incorporating parenting resources into integrated SU treatment programs. While promising, it is imperative to examine and test parenting programs in a variety of settings. This study examined whether SU moderated the relationship between treatment condition and parenting outcomes among parents who participated in SafeCare, and parent ratings of engagement, service satisfaction, and perceived cultural competency of services. Results indicated that SU did not moderate the relationship between treatment condition and abuse potential, but did moderate this relationship for depression and parental distress such that parents with higher levels of SU reported less improvement in depression and parental distress. Results underscore that SU problems may impact the effectiveness of SC on specific risk factors, such as depression and parental distress, potentially indicating unique treatment needs and the need to adapt interventions to ensure treatment success. In addition, this study found that SafeCare was not found to be beneficial for parents with SU problems above and beyond the treatment as usual condition. Finally, results indicated that parents with SU concerns and without SU concerns engaged very similarly in SafeCare.